Hubungan Determinan Sosial Kesehatan dengan Infeksi Toksoplasma gondii - Jasmine, Almaina Puteri; Mutiara, Hanna; Suwandi, Jhons Fatriyadi; Putri, Giska Tri (Medula, 2024)
Toxoplasma gondii is an obligate intracellular protozoan that causes toxoplasmosis. The high rate of toxoplasmosis infection in the Lampung region reaches 88.23%. Typically, toxoplasmosis presents no symptoms but can pose serious problems for individuals with compromised immune systems or pregnant women. The purpose of this study is to identify the relationship between social health determinant factors such as age, gender, educational level, occupation, and residence address with the incidence of T. gondii infection among patients at Dr. H. Abdul Moeloek Hospital. The aim is to identify individuals at risk of toxoplasmosis infection early so prevention can be done immediately. This study is an analitic quantitative research with a cross-sectional design. The study population consists of patients at Dr. H. Abdul Moeloek Hospital who have been screened for toxoplasmosis from 2017 to 2023, with a sample size of 93 samples. A total of 67 samples were tested positive for toxoplasmosis, while 26 samples tested negative with the sampling technique using total sampling. Data were collected from patients medical records and were analyzed by univariate and bivariate analysis using Chi-square method. The results indicate a relationship between age (p 0.002), gender (p <0.001), and educational level (p <0.001) with the incidence of Toxoplasma gondii infection among patients at Dr. H. Abdul Moeloek Hospital from 2017 to 2023.